Originator Performance, CMBS Structures, and the Risk of Commercial Mortgages - Titman, Sheridan; Tsyplakov, Sergey (Review of Financial Studies, 2010)
This article examines information and incentive problems that can exist in the market for commercial mortgages that are pooled and repackaged as commercial mortgage-backed securities (CMBSs). We find that mortgages that are originated by institutions with large negative stock returns in the quarters prior to the origination date tend to have higher credit spreads and default more than other mortgages with similar observable characteristics. Properties financed with these mortgages also exhibit weaker post-securitization operating performance. In addition, stock price loser institutions are anxious to securitize mortgages they originate more quickly. Finally we find that credit rating agencies require higher levels of subordination for CMBS pools (i.e., view these pools as riskier) that include more mortgages originated by underperforming originators. This evidence is consistent with reputation models in which poorly performing originators have less incentive to carefully evaluate the credit quality of prospective borrowers, thereby letting relatively riskier mortgages pass through their weaker screening standards.